‘Ev’ry Gamester winneth by the sport’: George Wither’s Emblem Lottery (1635) - Pierre Le Duff (Angles)
George Wither, a notoriously controversial poet of the 17th century, wrote in the introductory text to his Collection of Emblemes in 1635 that he was adding a “harmless […] recreation”, referring to the lottery game he included in his book, which contains two hundred emblems. Wither goes to great length to claim that his lottery is merely an innocent pastime that was added to the work to make it less “over-solid and serious”, but a careful examination of the game in relation to the rest of the volume reveals a more complex rhetorical and aesthetic purpose. The lottery game is allegorically represented in the middle of the frontispiece on the first page of the book, an intricate engraving by William Marshall representing the pilgrimage of life on the paths of virtue and vice, where the pilgrims draw their metaphorical lots from an ewer under the supervision of Fortune personified. As the frontispiece can be read as an emblematic representation of the volume, this mise-en-abyme contradicts the poet’s assertions about the lottery’s incidental nature, and therefore raises questions on its true place in the work. Through his game, Wither establishes a close, personal, often tongue-in-cheek and multi-faceted relationship with his readers, addressing them directly and creating the impression that the broad and general advice provided in the emblems is in fact tailored to their very personal needs. It is an original vector for social criticism and satire, and mirrors the author’s own religious and philosophical ambiguities with respect to notions such as free will, personal responsibility, and fortune. It grants the emblems a theatrical, dynamic, and social dimension that testifies to Wither’s profound understanding of the rhetorical possibilities granted to him both by the emblematic genre and by the nature of a game.